Moment Generating Function Approach in Diversity Combiner with M-PSK over Hoyt Fading Channel - Z.K, Adeyemo; A.S., Ajadi; F.A, Semire; S.I., Ojo (Discoveries in Agriculture and Food Sciences, 2019)
Wireless communication system is the processing, transmitting and receiving signals over an open space. This system suffers from time varying environment disturbance due to propagation of signals through different paths which prompt the signals to have different statistical distributions. The existing modified diversity combiners diversity such as Maximal Ratio Combiner (MRC), Equal Gain Combiner (EGC) with one Match Filter (MF) and one Radio Frequency (RF) chain, lack closed form expression. Therefore, in this paper, Moment Generating Function (MGF) approach is used to analyse the performance of the modified MRC over Hoyt fading distribution through the closed form expression. A closed formed expression is developed using the existing modified MRC with one Radio Frequency (RF) chain and one Matched Filter (MF) at the RF stage. Binary data of ten thousand bits are generated randomly as source data and modulated with M-ary Phase Shift Keying (M-PSK). The modulated signal is passed through the Hoyt fading channel which is then modeled using Moment Generating Function (MGF) approach in order to generate the resultant signals. The resultant signals at varying paths ‘L’ (2, 3 and 4) and Hoyt fading factors’q’ (0.2, 0.4 and 0.6) are combined using the modified MRC. The output signal is passed through a comparator which compares the output signal with 9.5 dB set as threshold value. The outage probability of the modified MRC using M-PSK (2-PSK and 4-PSK) at varying ‘L’ and ‘q’ is evaluated, while processing time is used to compare the performance of the conventional MRC with the modified MRC. The results obtained with the modified MRC using closed form expression give lower Outage Probability (OP) and processing time. The research can be used by satellite communication system designers to improve the quality of service.